2017
DOI: 10.1038/onc.2017.221
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between NRF2 and HIPK2 shapes cytoprotective responses

Abstract: Homeodomain interacting protein kinase-2 (HIPK2) is a member of the HIPK family of stress-responsive kinases that modulates cell growth, apoptosis, proliferation and development. HIPK2 has several well-characterised tumour suppressor roles, but recent studies suggest it can also contribute to tumour progression, although the underlying mechanisms are unknown. Herein, we have identified novel crosstalk between HIPK2 and the cytoprotective transcription factor NRF2. We show that HIPK2 is a direct transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 73 publications
0
59
0
Order By: Relevance
“…Besides, HIPK2 is required for robust NRF2 responsiveness in cancer cells and in vivo. 58 HIPK2 also controls the levels of Notch1, a well-established factor with dual roles in cancer, that can act as both tumour suppressor and oncogenic factor, depending on the context. 59,60 These reports add strength to the notion that HIPK2 possesses context-dependent roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, HIPK2 is required for robust NRF2 responsiveness in cancer cells and in vivo. 58 HIPK2 also controls the levels of Notch1, a well-established factor with dual roles in cancer, that can act as both tumour suppressor and oncogenic factor, depending on the context. 59,60 These reports add strength to the notion that HIPK2 possesses context-dependent roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 56,57. Besides, HIPK2 is required for robust NRF2 responsiveness in cancer cells and in vivo 58. For example, HIPK2 is a downstream target of NRF2 (nuclear factor, erythroid 2 like 2), which is an important regulator of intracellular redox homeostasis and oncogenes in cancer.…”
mentioning
confidence: 99%
“…Indeed, HIPK2 is a well-characterized p53 regulator, promoting the expression of apoptosis-related p53-target genes [82]. Recently, it has demonstrated that HIPK2 ablation induces cerebellar dysfunction compatible with an ataxic-like phenotype [83] and, being a redox-sensitive kinase [84] Nrf2, which positively regulates its expression. HIPK2, in turn, supports Nrf2 cytoprotective activity, promoting its nuclear accumulation and activity [84].…”
Section: Nrf2 Cross-talks With Other Cellular Pathwaysmentioning
confidence: 99%
“…Recently, it has demonstrated that HIPK2 ablation induces cerebellar dysfunction compatible with an ataxic-like phenotype [83] and, being a redox-sensitive kinase [84] Nrf2, which positively regulates its expression. HIPK2, in turn, supports Nrf2 cytoprotective activity, promoting its nuclear accumulation and activity [84]. These data suggest that HIPK2 may be an important modulator of Nrf2 in the regulation of oxidative stress-related genes and correlated diseases.…”
Section: Nrf2 Cross-talks With Other Cellular Pathwaysmentioning
confidence: 99%
“…The cell lines were validated by STR profiling and were routinely tested to ensure that they were mycoplasma-negative. CRISPR-edited NRF2-knockout (NRF2-KO) and NRF2-gain-of-function (NRF2-GOF) DLD1 cell lines were produced as previously described [22].…”
Section: Cell Culturementioning
confidence: 99%